Urban Homicide in the United States, 1980-2010: The Importance of Disaggregated Trends. (August 2015) - Chilton, Roland; Chambliss, William J.
Using Centers for Disease Control and Prevention (CDC) mortality and census data with Supplementary Homicide Reports, we compare 25- and 30-year homicide trends for four age-race-sex categories in 172 U.S. cities. The comparisons indicate that one of the most salient aspects of homicide in the United States from 1980 to 2010 was the disproportionate involvement of young Black men as homicide victims and offenders. The persistence of these rates before, during, and after a sharp rise followed by a dramatic drop in the overall rates suggests the need for a focus on specific explanations for this aspect of urban homicide.